Hacía una técnica normativa a la colombiana: aproximación crítica a las propuestas de mejora normativa de la OCDE para Colombia (2020)
The discourse on development has been a constant in geopolitical relations in recent decades. Countries have been engaged in a competition to earn the title of developed nations and to escape from other classifications such as underdeveloped or developing. Despite the efforts of international and multilateral organizations to promote the so-called development, the path to achieve it is still not clear, since few countries have managed to move between the different classifications and in the existing cases the causal link between pro-development policies and their reclassification is not clear. This text intends, from the analysis of the process of normative improvement initiated by Colombia and promoted by the OECD, to show that this type of pro-development policies may have different effects than those desired, which can be explained by design flaws, associated with the purpose of imposing an infallible vision of development...